Optimization of montages and electric currents in tDCS. (October 2020) - Khorrampanah, Mahsa; Seyedarabi, Hadi; Daneshvar, Sabalan; Farhoudi, Mehdi
Abstract: In order to optimize the capability of transcranial Direct Current Stimulation (tDCS), electrode arrangements and the inward current stimulation are taken into account as two crucial factors. In this contribution, in order to specify the electrode positions, a detailed protocol is investigated, in which regarding the intended targeted regions, the optimal montages with an arbitrary number of electrodes are developed. After designing the positions of all active and returned electrodes, the corresponding inward current density is determined for each electrode. The outcomes of the simulation and the electric field distributions in the hand cortex prove that the proposed protocol is capable of improving the tDCS efficiency substantially in all head layers. Furthermore, in order to compare our approach with the other works found in the literature, a performance evaluation is curried out by calculating the maximum electric field distribution in the targeted region. This study shows that it improves tDCS efficiency virtually 2.5 times in comparison to High Definition (HD) montages in the gray matter and nearly 1.5 times in comparison to the other inner layers. Such an outstanding achievement in the gray matter can be regarded as an interesting standpoint in tDCS-rehabilitation studies. Highlights: The most effective and important factors of electric field distribution in targeted region are formulated. According to the targeted region, the optimal protocol is designed to predict the arrangement of electrodes in tDCS. The non-uniform electric currents for each electrode are calculated and performed to achieve the optimal stimulation. The proposed protocol has more focality and intensity in ROI than other montages such as HD-tDCS. The neuroscientists could have the right choice of the arrangements and inward currents of stimulation electrodes.